ПРАВОВІ ЗАСАДИ ВАЛЮТНОГО РЕГУЛЮВАННЯ ТА МІСЦЕ СЕРЕД НИХ АДМІНІСТРАТИВНО-ПРАВОВОГО РЕГУЛЮВАННЯ - Кібець, Дар'я Вікторівна (SUPREMANCE OF LAW, 2018)
In the article, based on the analysis of the norms of the current legislation of Ukraine, the legal principles of currency regulation in Ukraine are determined. It is emphasized that special role in currency regulation belongs to the norms of administrative law, because it is with their help it is possible to properly organize the activities of authorized entities, and also to ensure proper performance of their functions.
Keywords: constraints; legal principles; currency regulation; administrative-legal regulation; normative-legal act